Negative De Moivre

Algebra Level 2

2 cos π 6 i sin π 6 = ? \frac 2 { \cos \frac \pi 6 - i \sin \frac \pi 6 } = \ ?

3 3 4 i \frac { \sqrt { 3 } }{ 3 } -4i 4 3 3 + 4 i \frac { 4\sqrt { 3 } }{ 3 } +4i 3 i \sqrt { 3 } -i 3 + i \sqrt { 3 } +i 4 3 3 4 i \frac { 4\sqrt { 3 } }{ 3 } -4i

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

( c o s 0 i s i n 0 ) = 1 2 = 2 ( c o s 0 i s i n 0 ) 1 sin θ = sin θ a n d cos θ = cos θ ( cos π 6 i sin π 6 ) = ( cos π 6 + i sin π 6 ) = ( cos ( π 6 + 2 π ) + i sin ( π 6 + 2 π ) ) = ( cos 11 π 6 + i sin 11 π 6 ) 2 f r o m 1 a n d 2 x = 2 cos π 6 i sin π 6 = 2 ( c o s 0 i s i n 0 ) ( cos 11 π 6 + i sin 11 π 6 ) = 2 1 ( cos ( 0 11 π 6 ) + i sin ( 0 11 π 6 ) ) = 2 ( cos ( 11 π 6 ) + i sin ( 11 π 6 ) ) = 3 + i \huge{ \because (cos0-isin0)=1\\ \therefore 2=2(cos0-isin0)\rightarrow \boxed { 1 } \\ \because -\sin { \theta =\sin { -\theta } } and\cos { \theta } =\cos { -\theta } \\ \therefore (\cos { \frac { \pi }{ 6 } } -i\sin { \frac { \pi }{ 6 } ) } \\ =(\cos { -\frac { \pi }{ 6 } } +i\sin { -\frac { \pi }{ 6 } ) } \\ =(\cos { (-\frac { \pi }{ 6 } +2\pi } )+i\sin { (-\frac { \pi }{ 6 } +2\pi ) } )\\ =(\cos { \frac { 11\pi }{ 6 } } +i\sin { \frac { 11\pi }{ 6 } } )\rightarrow \boxed { 2 } \\ from\quad \boxed { 1 } \quad and\quad \boxed { 2 } \\ { x=\frac { 2 }{ \cos { \frac { \pi }{ 6 } } -i\sin { \frac { \pi }{ 6 } } } }\\ =\frac { 2(cos0-isin0) }{ (\cos { \frac { 11\pi }{ 6 } } +i\sin { \frac { 11\pi }{ 6 } } ) } \\ =\frac { 2 }{ 1 } (\cos { (0-\frac { 11\pi }{ 6 } ) } +i\sin { (0-\frac { 11\pi }{ 6 } ) } )\\ =2(\cos { (-\frac { 11\pi }{ 6 } ) } +i\sin { (-\frac { 11\pi }{ 6 } ) } )\\ =\boxed { \sqrt { 3 } +i } }

It is known that e i θ = cos θ + i sin θ e^{i\theta} = \cos{\theta}+i\sin{\theta} .

Therefore,

x = 2 cos π 6 i sin π 6 = 2 e i π 6 = 2 e i π 6 = 2 ( cos π 6 + i sin π 6 ) x = \dfrac {2}{\cos{\frac{\pi}{6}} - i\sin{\frac{\pi}{6}}} = \dfrac {2}{e^{-i\frac{\pi}{6}}} = 2e^{i\frac{\pi}{6}} = 2(\cos{\frac{\pi}{6}} + i\sin{\frac{\pi}{6}})

= 2 ( 3 2 + i 1 2 ) = 3 + i \quad = 2\left( \frac{\sqrt{3}}{2}+i\frac{1}{2} \right) = \boxed{\sqrt{3}+i}

2 cos π 6 i sin π 6 \dfrac{2}{\cos\frac{\pi}{6} - i\sin\frac{\pi}{6}} = 2 cos ( π 6 ) + i sin ( π 6 ) =\dfrac{2}{\cos(-\frac{\pi}{6}) + i\sin(-\frac{\pi}{6})} = 2 c i s ( π 6 ) =\dfrac{2}{cis(-\frac{\pi}{6})} = 2 ( c i s ( π 6 ) 1 ) =2(cis(-\frac{\pi}{6})^{-1}) = 2 c i s ( π 6 ) = 3 + i =2cis(\frac{\pi}{6})=\sqrt{3}+i

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...